CO2 capture cost saving through waste heat recovery using transport membrane condenser in different solvent-based carbon capture processes. (1st February 2021) - Cui, Qiufang; Tu, Te; Ji, Long; Yan, Shuiping
Abstract: In this study, the waste heat from the hot stripping gas was recovered by adopting the transport membrane condenser (TMC) in the monoethanolamine (MEA)-, diethanolamine (DEA)-, piperazine (PZ)- and potassium glycinate (PG)-based rich-split modified carbon capture processes. A 220-h test showed that TMC can exhibit a good stability on the waste heat recovery performance. The PZ-based TMC-modified rich-split process (i.e., PZ-case) achieved a highest waste heat recovery performance, followed by the PG-case, MEA-case and DEA-case. A strong linear relationship between the heat and water fluxes was observed during the waste heat recovery. Three scenarios were considered for comparing the CO2 capture cost savings of 4 cases. When the TMC area was fixed meaning the same additional investment of rich-split modification, PZ-case gained the highest CO2 capture cost saving ($6.40/t-CO2 ), followed by PG-, MEA- and DEA-case. When a fixed waste heat recovery performance of 600 kJ/kg-CO2 was required for obtaining the same revenue after rich-split modification, PZ- and PG-case obtained the same CO2 capture cost saving of $4.22/t-CO2 . Moreover, when the reboiler duty reduction potential was aimed at 15%, PG-case achieved the maximum CO2 capture cost saving ($4.56/t-CO2 ). Highlights: CO2 capture cost decreases by waste heat recovery using transport membrane condenser. Transport membrane condenser has a good stability on heat recovery performance. There is a strong linear relationship between the heat flux and the water flux. PZ-case achieves the best heat recovery performance among four solvent cases. A highest CO2 capture cost saving with $6.40/t-CO2 can be obtained for PZ-case.